PENGARUH LIFESTYLE, LITERASI KEUANGAN DAN PENDAPATAN TERHADAP PERILAKU KEUANGAN PELAKU BISNIS MUA KOTA SEMARANG - Salsa Bella Anindia; Khairina Nur Izzaty (Jurnal Akuntansi dan Bisnis, 2026)
The purpose of this study was to determine the influence of lifestyle, financial literacy, and income on financial behavior. The research method used was quantitative. Data collection was conducted through questionnaires distributed to Makeup Artist in Semarang City. The sample used in this study was 50 respondents. Analysis included validity, reliability, normality, multicollinearity, heteroscedasticity, and the coefficient of determination (R2). The F-test results in this study indicate that all X variables simultaneously have a significant positive effect on Y variable. The t-test results in this study indicate that lifestyle has no effect on financial behavior, while financial literacy and income have a positive effect on financial behavior.